Scientific justification of Mycobacterium avium survival in natural environment of Republic of Dagestan - M. O. Baratov; A. R. Mustafayev (Ветеринария сегодня)
Contamination of the environment with the infectious animal disease agents is still a pressing problem for the poultry farms. Mycobacterium avium can grow and replicate in organic wastes from the poultry farms for a long time thus contaminating vast adjacent areas and being the source of infection not only for wild and domestic animals but also for humans. The studies were aimed at the examination of the duration of Mycobacterium avium survival in the natural environment in two geographical regions of the Republic of Dagestan characterized by different soil and climate. Samples of Mycobacterium avium-contaminated feces and soil collected from pastures and farmyards (on the surface and from 5 cm depth) were tested. The experiments demonstrated that pathogenic for chickens mycobacteria survived for up to 30 days in the samples collected in the sub-mountainous areas in summertime, when the air temperature ranged from 15.1 to 30 °С, land surface temperature – from 17 to 38 °С, air humidity – from 44 to 94% and average monthly precipitation amounted to 1.5 mm. From September to May, with the air temperature ranging from –10.8 to +25 °C, land surface temperature from –14 to +30 °C, air humidity 26–100% and average precipitation 0.39 mm, the bacteria survived for up to 213 days on the soil surface on the pastures and farmyards, and for up to 243 days at the depth of 5 cm and in the feces. In the plain area, in the same time period in the slightly saline soil with high humus content and at air temperature from –11.9 to +27.3 °C, soil temperature from –13 to +45 °C, air humidity from 37 to 100% and average precipitation 20.4 mm, Mycobacterium avium survived just like in the sub-mountainous area, i.e. for 213 and 243 days, respectively. The post-mortem lesions in the internal organs of the poultry corresponded to the tuberculosis clinical signs in 86 of 171 birds (50.3%). The study results will allow for the development of the optimal algorithm for animal health and management measures aimed at tuberculosis eradication on the poultry farms.